STRENGTHENING EMPLOYEE COMMITMENT THROUGH FLEXIBLE WORK MODELS AND SUSTAINABLE HR PRACTICES IN INDONESIA STARTUPS - Iswahyudi; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (RADJA PUBLIKA, 2026)
This study examines the role of flexible work models and sustainable HR practices in enhancing employee commitment within Indonesian startups. As startups face increasing challenges in attracting and retaining talent, alternative HR strategies have become essential. Using a quantitative research approach, data were collected from employees across various startup sectors to analyze the relationship between flexible work arrangements, sustainable HR practices, and employee commitment. The findings indicate that flexible work models, such as remote and hybrid arrangements, positively influence work-life balance and autonomy, thereby strengthening affective commitment. Additionally, sustainable HR practices that emphasize employee well-being, fairness, and development further enhance engagement and retention. The study also finds that the combined implementation of flexibility and sustainability yields stronger outcomes than either approach alone. These results contribute to existing literature by integrating flexibility and sustainability within a single framework, particularly in the context of emerging startup ecosystems. The study provides practical implications for startup leaders in designing effective HR strategies. Overall, it highlights the importance of aligning organizational practices with employee expectations to foster long-term commitment and organizational success.